2nd Conference of the Slovenian Node of the European Research Infrastructure for Heritage Science E-RIHS Slovenia: Book of Abstracts (University of Maribor Press, 2025)
Heritage science is an interdisciplinary field that brings together humanities, natural sciences, and engineering. It focuses on research, preservation, and sustainable use of cultural and natural heritage. By doing so, we enhance our understanding and care for heritage, ensuring its preservation for future generations and improving its role in the lives of people today and in the future. In line with the mission of the European Research Infrastructure for Heritage Science (E-RIHS), ERIHS Slovenia also promotes collaboration among researchers from diverse disciplines and facilitates access to state-of-the-art research infrastructure, thereby strengthening the research culture. The book of abstracts is a collection of presentations held at the 2nd E-RIHS.si conference on the latest research in cultural heritage, including innovative solutions enabled using artificial intelligence.